The Typology of Banking Crimes in the Disruptive Era: A Comprehensive Review of Criminal Modi Operandi and Law Enforcement Challenges - Ruslan Mustari; Ali Rahman (Journal of Law, Politic and Humanities, 2026)
Banking crime is a global phenomenon that continuously mutates alongside technological disruption and economic dynamics. This article presents a comprehensive review of banking crime typologies through a conceptual and analytical approach to current academic literature. The focus of the study encompasses the constellation of money laundering, banking fraud, cybercrime, white-collar crime, terrorism financing, and corruption. The synthesis results indicate that criminal modi operandi have radically transformed, shifting from traditional models to the exploitation of regulatory loopholes (regulatory arbitrage), trade-based money laundering (TBML), the exploitation of money mules, and the abuse of digital instruments. Conversely, the primary challenges in law enforcement include regulatory lag, the borderless evolution of criminal technology, and institutional reluctance to report internal fraud to preserve corporate reputation. This review asserts that a comprehensive understanding of crime typologies is a fundamental prerequisite for formulating effective policies. Therefore, holistic legal reform is recommended through a shift toward a risk-based supervisory framework, the strengthening of the corporate criminal liability doctrine, and the mandated adoption of integrated RegTech and SupTech to secure the stability of the national financial architecture.